The Effectiveness of a Qiyasiyah Based Instructional Model on Nahwu Mastery: A Quasi Experimental Study among Madrasah Diniyyah Al Amiriyyah Students - Elmas Maisya Al Bareza; M. Alaika Nashrulloh; Abdul Basith; Nik Muhammad Rozi Bin Nik Yusoff (Institut Agama Islam Negeri Curup, 2026)
Reliance on traditional rote learning methods hinders students' analytical reasoning skills in mastering Nahwu. Therefore, a systematic integration of the analogical approach (qiyas) and modern pedagogy is required to bridge the instructional gap that has, until now, been addressed in isolation. This study aims to test the effectiveness of the Qiyasiyah - Based Instructional Model, which combines analogical reasoning with active learning principles, This study aims to test the effectiveness of the Qiyasiyah Based Instructional Model in improving Nahwu mastery. Using a quasi-experimental design (pretest-post-test control group), the study involved 58 female students from Madrasah Diniyyah Al Amiriyyah who were divided into an experimental group (receiving Qiyasiyah Based Instructional Model) and a control group (conventional method). The data were analyzed using independent sample t-tests and effect size calculations (Cohen's d). The results showed a statistically significant improvement (p < 0.001) in the experimental group with a large effect size (d = 1.58), and more even achievement than in the control group. These findings indicate that the Qiyasiyah Based Instructional Model is effective in improving students' understanding of Nahwu rules within the context of Madrasah Diniyyah Al Amiriyyah. The study concludes that the Qiyasiyah Based Instructional Model provides a structured, evidence - based pedagogical framework for improving Nahwu learning in the context of Madrasah Diniyyah Al Amiriyyah. The implications support the adoption of this model in the curriculum and teacher training, with recommendations for further research that expands the sample size and context of application.